2017
DOI: 10.1002/hec.3622
|View full text |Cite
|
Sign up to set email alerts
|

The effect of parental education on child health: Quasi‐experimental evidence from a reduction in the length of primary schooling in Egypt

Abstract: This paper examines the impact of parental education on child health using a reduction in the length of primary schooling in Egypt. We use a fuzzy regression discontinuity design to compare the health outcomes of children whose parents were exposed to different schooling requirements because they were born either side of a threshold date. Using data from the Demographic and Health Survey (1992-2014), we find no effect of maternal education on child mortality or nutritional status. There is some evidence, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…Given the small number of studies and the criteria listed above, we were only able to conduct meta‐regressions for five of the 17 infant and child health outcomes in seven papers . Consistent with that observed in the forest plots, meta‐regression results indicate a statistically significant mean effect size of increased grade attainment only on child mortality measured dichotomously: −0.0206 ( P = 0.018).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Given the small number of studies and the criteria listed above, we were only able to conduct meta‐regressions for five of the 17 infant and child health outcomes in seven papers . Consistent with that observed in the forest plots, meta‐regression results indicate a statistically significant mean effect size of increased grade attainment only on child mortality measured dichotomously: −0.0206 ( P = 0.018).…”
Section: Resultsmentioning
confidence: 68%
“…Of the final set of 16 papers, only one study investigating maternal morbidity, and no papers on maternal mortality or malaria, met our inclusion criteria. Of the papers that examined child health, seven investigated the effects of education on both infant and child mortality [35,36,[49][50][51][52][53], one measured child but not infant mortality separately [54] and one measured infant but not child mortality [55]. Of the nine papers that investigated infant mortality [35, 36, 49-53, 55, 56], five also examined neonatal mortality [35,36,51,52,56].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For youth educational outcomes, parental education is one of the most significant resources that shape youth educational (Mercy and Steelman, 1982;Davis-Kean, 2005) and health (Wills et al, 1995;Appleton-Arnaud, 2008;Ali and Elsayed, 2018) outcomes. In line with MDRs framework, however, researchers have documented smaller health gains from parental educational attainment for AA than non-Hispanic White adolescents (Assari, 2018b,c;Assari and Hani, 2018;Assari et al, 2018a,b,e).…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt and Peru, for instance, low under-five survival was observed in areas with high levels of educational attainment (upper left corner in Fig 1), in particular for girls under five (see S4 Fig for results disaggregated by a child's sex in Egypt and Peru) [34]. Although this finding appears counterintuitive, a growing literature suggests mixed child health returns to additional years of maternal schooling [35][36][37][38]. A recent systematic review examined evidence for a causal link between maternal education and child health and found that parental schooling may play a more muted role in parents' decisions about whether and how much to invest in their children's health than previously suggested [39].…”
Section: Discussionmentioning
confidence: 98%